The mathematical and theoretical biology institute - a model of mentorship through research - Erika T. Camacho; Christopher M. Kribs-Zaleta; Stephen Wirkus (Mathematical Biosciences and Engineering)
This article details the history, logistical operations, and design philosophyof the Mathematical and Theoretical Biology Institute (MTBI), a nationallyrecognized research program with an 18-year history of mentoring researchers atevery level from high school through university faculty, increasing the numberof researchers from historically underrepresented minorities, and motivating them to pursue research careers by allowing them to work on problems of interest to them and supporting them in this endeavor. This mosaic profilehighlights how MTBI provides a replicable multi-level model for research mentorship.